2004
DOI: 10.1590/s1413-294x2004000200008
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes de estudantes universitários frente ao consumo de materiais pornográficos

Abstract: ResumoA expansão do mercado de produtos pornográficos traz à tona a discussão acerca da influência dos valores transmitidos pela mídia no comportamento dos indivíduos. A questão da pornografia permanece sem o devido aprofundamento, pois o Brasil ainda é carente de pesquisas nesta área. Este estudo descreve a elaboração e validação de um instrumento de medida das atitudes frente ao consumo de materiais pornográfi-cos, aplicada a 336 universitários e os dados submetidos à análise fatorial. Os 33 itens construído… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
7
0
8
Order By: Relevance
“…From another point of view, a research carried out in Paraíba with university students of both genders showed that consumers of sexual media disagree with the idea that pornography brings harmful effects such as addiction, trivialization of sex and, damage to relationships and sexual formation, the opposite perspective of non-consumers, who perceive this consumption as harmful. It was found that the research sample minimized the influence of SEM on their own sexual behaviors (24) .…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, a research carried out in Paraíba with university students of both genders showed that consumers of sexual media disagree with the idea that pornography brings harmful effects such as addiction, trivialization of sex and, damage to relationships and sexual formation, the opposite perspective of non-consumers, who perceive this consumption as harmful. It was found that the research sample minimized the influence of SEM on their own sexual behaviors (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The individual experiences in conjunction with the cultural context, which is characterized by the system of shared beliefs, social norms, values and expectations regarding the right way to behave in certain situations, form our identities in addition to the influence on the part of parents, friends, institutions (e.g. school and church) and mass communication systems (Guerra, Andrade & Dias, 2004). In this sense, the core issue is to question if the consumption of pornography can be seen as an influencer that enables people, based on their own experiences and interpretations of sexuality, to alter their sexual behavior progressively over time.…”
Section: Pornography and Consumptionmentioning
confidence: 99%
“…Usou-se a Escala de Atitudes Face ao Uso de Materiais Pornográficos (Guerra, Andrade, & Dias, 2004), com 27 itens, que mede as atitudes face à pornografia através de duas escalas.…”
Section: Atitudes Face à Pornografiaunclassified